2018
DOI: 10.1021/jacs.8b05812
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Structural and Energetic Basis of Allostery in a De Novo Designed Metalloprotein Assembly

Abstract: Despite significant progress in protein design, the construction of protein assemblies that display complex functions (e.g., catalysis or allostery) remains a significant challenge. We recently reported the de novo construction of an allosteric supramolecular protein assembly (Zn-R1) in which the dissociation and binding of Zn ions were coupled over a distance of 15 Å to the selective hydrolytic breakage and formation of a single disulfide bond. Zn-R1 was constructed by Zn-templated assembly of a monomeric pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 68 publications
2
12
0
Order By: Relevance
“…To understand the energetic basis of allosteric coupling in C38/C81/C96 R1 4 , we carried out extensive molecular dynamics calculations, which revealed that allostery was governed by an entropy/enthalpy trade-off . This trade-off primarily involves the hydrophobic i 1 interfaces, which rearrange upon Zn II dissociation to form favorable packing interactions that overcome the energetic cost incurred by reduced configurational freedom of the assembly.…”
Section: Construction Of Allosteric Metalloproteinssupporting
confidence: 59%
“…To understand the energetic basis of allosteric coupling in C38/C81/C96 R1 4 , we carried out extensive molecular dynamics calculations, which revealed that allostery was governed by an entropy/enthalpy trade-off . This trade-off primarily involves the hydrophobic i 1 interfaces, which rearrange upon Zn II dissociation to form favorable packing interactions that overcome the energetic cost incurred by reduced configurational freedom of the assembly.…”
Section: Construction Of Allosteric Metalloproteinssupporting
confidence: 59%
“…As this strategy is predicated upon the use of well-folded protein building blocks and natural amino acids, its application in the laboratory evolution of enzymatically-active metalloproteins operative in oxidative or hydrolytic processes can be readily envisioned. 35…”
Section: Discussionmentioning
confidence: 99%
“…The main advantage is, of course, that the assembly process becomes controllable by an external cue, for example, the concentration of a bivalent drug 23 , or even multiple cues, such as metal concentration, pH and chelators 21,22 , or metal identity, redox potential, and mechanical stress 28 . The combination of two of these mechanisms leads to even more sophisticated behavior, such as the re-creation of an allosteric transition by introducing structural strain between metal binding and disulfide bond formation on a designed protein tetramer 29,30 .…”
Section: Introductionmentioning
confidence: 99%